Do Internal Factors Improve Employee Performance? - ningsih, Fitri Susilawati; Turmudhi, Anis (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Human resources have an instrumental role in the development and progress of organizations, both large and small. Every company or institution strives to achieve success in a way that does not quickly increase the productivity of its employees. This research explores companies' initiatives to improve employee performance and human resource management at St. Augustine Catholic University Pontianak. Using quantitative methods and census sampling techniques, this study involved the entire population of Santo Augustine University Pontianak employees, which amounted to 65 people, as a sample. The findings show that Motivation, Discipline, and Teamwork positively improve employee performance. Motivation and Discipline have been shown to significantly improve employee performance, while Teamwork has a positive but insignificant effect on employee performance.